Sarcoidosis and increased risk of comorbidities and mortality in Sweden : Sarcoidosis - Comorbidities and Mortality - Larsson, Johanna; Graff, Pål; Bryngelsson, Ing-Liss; Vihlborg, Per (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Introduction: Sarcoidosis is a systemic inflammatory disorder, with an unclear etiology, involving granuloma formation that in most cases affects the lungs and intrathoracic lymph nodes. Sarcoidosis occurs in an acute or chronic form, each with different clinical presentation and prognosis. Methods: Case-control study of comorbidity and mortality in people diagnosed with sarcoidosis (ICD10 code D86) from 2007 through 2016 in Sweden. Controls were matched to cases (2:1) based on age, sex and county at the time of diagnosis. Data was collected from the Swedish National Patient Register and The Cause of Death Register. All men and women aged 20-65 years old who were diagnosed with sarcoidosis (D86, ICD10) during the years of study were included, resulting 7828 cases and 15656 controls. Results: Patients with sarcoidosis had increased mortality compared to matched controls (hazard ratio 1.88; 95% CI 1.56 – 2.26) and the Swedish general population (standardized mortality ratios1.75; 95% CI 1.52 – 2.00). The sarcoid cases, compared to controls, also had a significantly greater number of inpatient visits within several different chapters of ICD10 e.g. cardiomyopathy, heart failure, pulmonary embolism and malignant neoplasm. Conclusion: Individuals with sarcoidosis are at higher risk of comorbidities and mortality than matched controls as well as the general population of Sweden. These findings are important knowledge for healthcare professionals who meet sarcoid patients, to encourage identification and treatment of comorbidities to reduce the risk of impaired quality of life and, eventually, premature death.